A ressocialização por meio da educação escolar no sistema penitenciário do Tocantins: um estudo de caso - Santos, Nelcyvan Jardim dos (Universidade Federal do Tocantins, 2016)
This thesis presents the practical arguments and theoretical foundations that support the rehabilitation through education in the prison of Tocantins system , harmonized with the constitutional provision of access to basic formal education in its widest and prison education policy through technological methods capable of meet the needs of educational development to those who are deprived of freedom, it has advantages over the classroom teaching and expands the access to schooling through this mode. Although access to education in prisons be found stamped on the Universal Declaration of Human Rights , the Penal Execution Law , the Law of Directives and base of National Education , and other regulations, it is necessary to show that these individuals left in the background by society also have rights , capacity and real possibility of a harmonious social integration. The research design includes a qualitative approach with exploratory purpose and also the bibliographical and documentary research; the problem was investigated as an object of study to understand and analyze the rehabilitation program through school education in resocialization Center Light of Tomorrow (CRLA) in structurally and from the point of view of the speeches of the students. The characteristics of the phenomenon, achieved greater understanding and accuracy, especially on the study of internal reeducation regarding the potential difficulties faced within ressocializador. After analyzing the data, explanations of the causes and consequences has proposed an Action Plan for Education Distance deployment in Correctional Centres of Tocantins, in order to improve and enhance the education of public policies in the existing prison. Furthermore, to optimize the expansion of this type of education to reduce the violation of human rights of the students and minimize the lack of educational provision in state prisons.